2008
DOI: 10.1007/s10764-008-9314-1
|View full text |Cite
|
Sign up to set email alerts
|

Food Preferences and Nutrient Composition in Captive White-handed Gibbons, Hylobates lar

Abstract: We aimed to assess spontaneous food preferences in captive whitehanded gibbons and to analyze whether they correlate with nutrient composition. Via a 2-alternative choice test, we repeatedly presented 3 male Hylobates lar with all possible binary combinations of 10 types of food that are part of their diet in captivity and found the following rank order of preference: grape > banana = fig > apple > pear > honeydew melon > carrot > tomato > cucumber > avocado. Correlational analyses revealed a highly significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…As well-documented frugivores, fruits (especially ripe fruits), account for more than 50% of gibbons’ diet, except for the more folivorous siamang ( Symphalangus syndactylus ) [ 63 - 66 ]. It is commonly agreed that food choices of primates are correlated with the nutritional and toxic contents [ 65 , 67 , 68 ]. Compared with other parts of plant, fruits typically have the highest content of soluble carbohydrates, i.e., sweet tasting compounds [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…As well-documented frugivores, fruits (especially ripe fruits), account for more than 50% of gibbons’ diet, except for the more folivorous siamang ( Symphalangus syndactylus ) [ 63 - 66 ]. It is commonly agreed that food choices of primates are correlated with the nutritional and toxic contents [ 65 , 67 , 68 ]. Compared with other parts of plant, fruits typically have the highest content of soluble carbohydrates, i.e., sweet tasting compounds [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies, however, have demonstrated significant physical differences between free‐ranging and captive populations including that free‐ranging animals grow for longer periods of time (Altmann et al,1981; Cheverud et al,1992), mature later (Altmann et al,1981; Altmann and Alberts,2005) and have delayed dental eruption (Phillips‐Conroy and Jolly,1988; Zihlman et al,2004). Several behavioral aspects of feeding can differ in captivity as well, including manual manipulation of food and posture during feeding (Kerridge,1997), ability to forage and locate food items (Snowdon,1994; Britt and Iambana,2003), food choice (Fernandes,1996; Jildmalm et al,2008), and the social context of feeding (Brent et al,1993; Carlstead,1996; Yamamoto and Lopes,2004). Collectively, these observations demonstrate the potential for differential growth and behavioral development to impact feeding behaviors in captive versus wild primates.…”
Section: Potential Differences Between Laboratory and Natural Environmentioning
confidence: 99%
“…Furthermore, the nutrient composition of cultivated fruits and vegetables is well-established (Food Standards Agency, 2002) whereas that of plants consumed by primates in the wild is often unknown. Studies that adopted the approach to present cultivated fruits and vegetables to captive animals found that some primate species such as white-handed gibbons (Hylobates lar), ringtailed lemurs (Lemur catta), and pigtail macaques (Macaca nemestrina) display significant positive correlations between their food preferences and carbohydrate content (Hansell et al, 2020;Jildmalm et al, 2008;Laska, 2001) and are thus selective feeders with regard to their preferred source of metabolic energy. Other primate species such as spider monkeys (Ateles geoffroyi) and squirrel monkeys (Saimiri sciureus), in contrast, displayed significant positive correlations with total energy content (Laska, 2001;Laska et al, 2000) and are thus opportunistic feeders with regard to their preferred source of metabolic energy.…”
Section: Introductionmentioning
confidence: 99%